2005
DOI: 10.1084/jem.20042309
|View full text |Cite
|
Sign up to set email alerts
|

Identification of proteoglycans as the APRIL-specific binding partners

Abstract: B cell activating factor of the tumor necrosis factor (TNF) family (BAFF) and a proliferation-inducing ligand (APRIL) are closely related ligands within the TNF superfamily that play important roles in B lymphocyte biology. Both ligands share two receptors—transmembrane activator and calcium signal–modulating cyclophilin ligand interactor (TACI) and B cell maturation antigen (BCMA)—that are predominantly expressed on B cells. In addition, BAFF specifically binds BAFF receptor, whereas the nature of a postulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
315
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 327 publications
(333 citation statements)
references
References 52 publications
12
315
0
3
Order By: Relevance
“…42,43 Mesangial cell-derived APRIL may promote survival and proliferation in an autocrine or paracrine, e.g., proteoglycan-receptor-mediated, manner leading to increased glomerular cellularity. 6,44,45 On the other hand, the expression of BLyS and BAFF-R in inflammatory cells of the interstitium in lupus nephritis, as described by us, may help sustain autocrine B 31 and T lymphocytemediated inflammation in the tubulointerstitial compartment of kidneys with lupus nephritis. In the glomerular compartment, few T cells, even fewer B cells and no dendritic cells are typically present.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…42,43 Mesangial cell-derived APRIL may promote survival and proliferation in an autocrine or paracrine, e.g., proteoglycan-receptor-mediated, manner leading to increased glomerular cellularity. 6,44,45 On the other hand, the expression of BLyS and BAFF-R in inflammatory cells of the interstitium in lupus nephritis, as described by us, may help sustain autocrine B 31 and T lymphocytemediated inflammation in the tubulointerstitial compartment of kidneys with lupus nephritis. In the glomerular compartment, few T cells, even fewer B cells and no dendritic cells are typically present.…”
Section: Discussionmentioning
confidence: 72%
“…4 APRIL may also bind to heparan sulfate proteoglycans. 6,7 The receptors for BAFF and APRIL are mainly expressed on B cells. 4 In addition to the well established role in B-cell survival, these factors exert functions on different subsets of cells, eg, T cells 4,5 and monocytes.…”
mentioning
confidence: 99%
“…22 Signaling through TACI requires a trimerization of the receptor. [23][24][25] It is thus possible that inclusion of even one mutant receptor might affect the signaling by the complex. This might suggest a route of action for the R202H mutation, which is situated in the intracellular part of the protein.…”
Section: Discussionmentioning
confidence: 99%
“…Whether our present data can be extended to other myeloma growth factors is under active investigation in the laboratory. Two recent studies demonstrated that APRIL, a growth factor for myeloma cells (Moreaux et al, 2004), can bind HSPG (Hendriks et al, 2005;Ingold et al, 2005). One study reported that IL-6, the major known MMC growth factor (Klein et al, 1989), is a heparin-binding cytokine and that a heparin mimetic inhibits the biological activity of IL-6 and the binding to its receptors (Mummery and Rider, 2000).…”
Section: Discussionmentioning
confidence: 99%